Morte e morrer: opinião dos profissionais de saúde de uma unidade de terapia intensiva pediátrica - Scudeler, Débora Nunes [UNESP] (Universidade Estadual Paulista (Unesp), 2011)
Presently, the dying process and death most often occur in hospitals and, particularly, in Intensive Care Units (ICU), where patients’ lives are prolonged thanks to advanced technological devices and highly efficient medicines. To learn about the opinion of health care professionals working at a Pediatric Intensive Care Unit in relation to the dying process and dying. This is a descriptive quantitative study. A questionnaire was applied to the unit’s staff members from June to August, 2011. Data were statistically analyzed. Twenty-five professionals answered the questionnaire, and 72% faced death as a natural life process. 60% felt compassion, but that feeling did not interfere with how they cared for patients. Concerning their professional training, 52% reported not to have received any concerning patients’ caregivers in the dying process or death; therefore, they experienced such situation when they were already working, and 76% reported to be interested in updating courses on that theme. Further discussion about this topic during academic education is necessary. It is also necessary to provide health care professionals with specialization courses, debates and experience exchange so that they can better understand and deal with their feelings and limitations in face of death and thus give better care to patients and relate to patients’ families during the dying process of a loved one

O processo de morrer e a morte hoje acontecem na maioria das vezes em hospitais e principalmente nas Unidades de Terapia Intensiva (UTI), onde o paciente tem sua vida prolongada graças aos aparelhos tecnológicos avançados e aos medicamentos altamente eficazes. OBJETIVO: Conhecer a opinião dos profissionais de saúde que trabalham em uma Unidade de Terapia Intensiva Pediátrica em relação ao processo de morte e morrer. Trata-se de um estudo descritivo e quantitativo. Foi aplicado questionário aos funcionários da unidade, no período de junho a agosto de 2011. Os dados foram analisados estatisticamente. responderam o questionário 25 profissionais, sendo que 72% deles encaram a morte como um processo natural da vida e 60% sentem compaixão, mas, esse sentimento não interfere na forma como cuidam do paciente. Sobre a formação profissional, 52% relataram não ter recebido preparo algum sobre o cuidador do paciente no processo de morte e morrer, tendo então, vivenciado esta situação já trabalhando e 76% afirmam interesse em realizarem cursos de atualizações sobre o tema. É necessário maior discussão do tema na formação acadêmica. Também se faz necessário propiciar aos profissionais de saúde cursos de especialização, debates e trocas de experiências, para que esses profissionais possam melhor compreender e lidar com seus sentimentos e limitações perante a morte. E assim melhor cuidar dos pacientes e relacionar-se com a família durante o processo do fim da vida de um ente querido
Keywords: Enfermagem pediatrica; Unidade de tratamento intensivo; Emergencias pediatricas